A Systematic Review of Pragmatic Competence in Second Language Acquisition - Tisya Amalia Putri Sitorus; Deasy Yunita Siregar; Dea Nita Aulia; Nazwa Atalia Zahra; Aghna Ilmi Parinduri; Dini Nur Aini Lubis; Futri Dina Wardiah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This article presents a systematic review of pragmatic competence in second language acquisition (SLA), emphasizing its critical role in effective communication and intercultural understanding. Pragmatic competence encompasses the ability to understand and use language appropriately in diverse social and cultural contexts, including mastering speech acts, politeness strategies, conversational implicatures, and intercultural pragmatics. Despite its importance, pragmatic competence often receives less attention in language instruction compared to grammar and vocabulary. The review highlights the effectiveness of explicit and implicit teaching methods, authentic interaction, and cultural immersion in developing pragmatic skills. It also underscores the role of technology, such as digital platforms and simulations, in enhancing learners’ ability to navigate real-life communication scenarios. The findings reveal significant challenges, including cultural variability in pragmatic norms, difficulties in standardizing assessments, and the influence of learners’ individual differences. The study calls for innovative teaching and evaluation methods, focusing on personalized approaches and the integration of pragmatic learning with emotional intelligence. By synthesizing current research and practices, this article provides valuable insights for educators, curriculum developers, and researchers, advocating for adaptive, culturally informed, and technology-supported strategies to enhance pragmatic competence in SLA.